Privatisation handbook - National Council on Privatisation (Nigeria) (Kaduna, Nigeria : the regent, 2000)
This book is a handbook containing a detailed guidelines, policies and framework on national council on privatization.
"Published for National Council on Privatisation."
asm; 10/04/19
Ref.
Keywords: Privatization